PPP as a Creative Financing Innovation in The Financing of Makassar Parepare Railway Infrastructure - Helmi Adam; Henny Wang; Mega Fauziah; Octen Suhadi (International Journal of Business and Applied Economics, 2023)
Provision of infrastructure is needed to accelerate economic growth, improve people's welfare, and realize the availability of better public services. The involvement of the private sector as an innovation in infrastructure development will create better public services. The Government of Indonesia introduced the Public - Private Partnership (”PPP”) scheme in the provision of infrastructure to provide a room for the Government to cooperate with the private sector based on the principle of proportional risk allocation. The PPP project with the Availability Payment (AP) scheme is something new in Indonesia. PT Celebes Railway Indonesia (PT CRI) with its project" Makassar-Parepare Railway " is the first project to use this scheme.